DINAMIKA MEDIA FOTO RELATION HUMAS POLRES BAUBAU DAN MEDIA LOKAL - Aldin Aldin; Muh. Hidayatullah; Hastuti Hastuti (specta, 2025)
DYNAMICS OF MEDIA RELATIONS BETWEEN BAUBAU POLICE PUBLIC RELATIONS AND LOCAL MEDIA. This study analyzed a survey entitled "DYNAMICS OF MEDIA RELATIONS PUBLIC RELATIONS OF BAUBAU POLICE AND LOCAL MEDIA". This study was conducted using a descriptive qualitative approach. The aim is to describe in depth and comprehensively the dynamics of media relations between the Baubau Police Public Relations and local media, especially in conveying information to the public through mass media. With this approach, researchers can dig up detailed information through direct interaction with informants and analyze data narratively. Based on the results of the study on the dynamics of media relations between the Baubau Police Public Relations and local media, several conclusions can be drawn, including the dynamics of media relations between the Baubau Police Public Relations and local media in building public trust have produced positive results, but are formal and one-sided. The Baubau Police Public Relations strategy in influencing the effectiveness of media relations and local media decisions in publishing information is still centered on the speed of information distribution and personal relationships with journalists. However, this strategy is insufficient if it is not supported by the quality of information that meets journalistic standards.